2018
DOI: 10.1093/jamia/ocy088
|View full text |Cite
|
Sign up to set email alerts
|

A usability and safety analysis of electronic health records: a multi-center study

Abstract: To characterize the variability in usability and safety of EHRs from two vendors across four healthcare systems (2 Epic and 2 Cerner). Twelve to 15 emergency medicine physicians participated from each site and completed six clinical scenarios. Keystroke, mouse click, and video data were collected. From the six scenarios, two diagnostic imaging, laboratory, and medication tasks were analyzed. There was wide variability in task completion time, clicks, and error rates. For certain tasks, there were an average of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(124 citation statements)
references
References 7 publications
1
118
1
4
Order By: Relevance
“…The current variability in EHR usability across health care systems and vendors has been shown to be wide, with certain tasks having an average of a 9-fold difference in time and 8-fold difference in clicks between different EHRs. 42 Therefore, the unacceptably low scores with wide variation reported here are likely representative of the current state of EHR usability; namely, that usability is generally poor but that there is a wide range of EHR usability across systems, specialties, and practice settings. In comparison to other technologies, current EHRs are still in a nascent form and are only going to become more complex moving forward.…”
Section: Discussionmentioning
confidence: 85%
“…The current variability in EHR usability across health care systems and vendors has been shown to be wide, with certain tasks having an average of a 9-fold difference in time and 8-fold difference in clicks between different EHRs. 42 Therefore, the unacceptably low scores with wide variation reported here are likely representative of the current state of EHR usability; namely, that usability is generally poor but that there is a wide range of EHR usability across systems, specialties, and practice settings. In comparison to other technologies, current EHRs are still in a nascent form and are only going to become more complex moving forward.…”
Section: Discussionmentioning
confidence: 85%
“…Consistent with earlier efforts [6][7][8][9], examinations of patient safety reports continue to find evidence of a strong impact of usability problems on EHR safety [10,11]. A laboratory study of two commonly-used EHRs in four healthcare systems found wide variability in task completion time, required clicks, and error rates (ranging from 0% to 50% for various tasks), even though the products had been certified by accreditation authorities [12]. Overly burdensome and often inconsistent EHR documentation practices have also been discussed as a potential source of physician stress and safety risks [13][14][15].…”
Section: Clinical Informaticsmentioning
confidence: 53%
“…We also acknowledge that this study was conducted at only one institution with one EHR system. Previous research [48] shows wide variation in how different institutions use the same EHR product in different ways and how different EHR products offer different functionalities. Another limitation is that this EHR system was implemented only one year before we conducted this study.…”
Section: Limitations and Opportunities For Further Researchmentioning
confidence: 99%